ANALISIS DAMPAK NUTRISI TEHADAP STUNTING PADA ANAK USIA DINI DI KB TUNAS COMDECA LEBAKHARJO AMPELGADING-MALANG - Susanti, Yayuk; Yulia, Nikmahtul Khoir Tri (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
Fulfillment and introduction of nutrition to prevent stunting, adequate nutritional intake is very much needed by children for the process of normal and optimal child growth and development. The purpose of the analysis of the impact of nutrition on stunting at KB Tunas Comdeca. Researchers use qualitative narrative-descriptive research methods in describing the results of data through observation, interview, and documentation activities that researchers have conducted for 3 months. The focus of research on this project is so that children at an early age can avoid stunting and other chronic diseases such as obesity and malnutrition. The results of this analysis activity, parents provide healthy food every day to children according to the number of portions of food for children per serving, and schools will also make the nutrition improvement program a stunting prevention program at school. and collaborate with the integrated health post. For the development of children who experience stunting, they must use regular medical check-ups on every integrated health post agenda and carry out complete immunizations which are carried out once a month, and at school, activities to check weight, height, and LILA measurements are carried out once every 3 months so that children's growth and development can be detected periodically. The related suggestion from this study is that nutrition can be used as the main program in learning and can be communicated.